The Influence of Audit Opinion, Financial Distress, Company Growth, and Going Concern Opinion on Auditor Switching - Lambok DR Tampubolon (GoAcademica Research & Publishing, 2023)
The purpose of this study is to analyze the effect of audit opinion, financial distress, company growth, and going concern opinion on auditor switching in companies listed on the IDX. In this study using secondary data in the annual reports of manufacturing companies sourced from www.idx.co.id. The population in this study were 42 companies in the consumer goods sector listed on the Stock Exchange 2017-2019 and the samples obtained were 24 companies. The sampling method used in this research is purposive sampling method. The research analysis method used logistic regression analysis. The results of the analysis in this study indicate that audit opinion, financial distress, company growth and going concern opinion do not have a significant effect on auditor switching.